Localization in Yersinia pestis of peptides associated with virulence. - Straley, S C (1982)
An avirulent guanine auxotroph of wild-type Yersinia pestis was used to select isogenic mutants lacking invasive determinants of virulence including V and W antigens (Vwa-), genetically linked fibrinolysin, coagulase, and pesticin activities (Pst-), and the capacity to absorb exogenous pesticin and pigments including hemin (Pgm-). After growth in environments known to favor expression of these factors by the parent, cells were converted to spheroplasts and disrupted to obtain preparations of cytoplasm; particulate matter was separated into inner and outer membranes by sucrose gradient centrifugation. Peptides present in these fractions were then solubilized and compared by two-dimensional polyacrylamide gel electrophoresis. Components unique to Vwa+ cells, including V antigen, were restricted to the cytoplasmic fraction. In contrast, peptides possibly corresponding to fibrinolysin and coagulase were located primarily within the outer membrane of the Pst+ parent; pesticin was not identified. Similarly, a major outer membrane peptide, possibly representing the pesticin and pigment receptor, was peculiar to the Pgm+ parent. Accordingly, two of the virulence factors examined (Pst+ and Pgm+) can interact directly with host cells or fluids by virtue of their location on the bacterial surface. The remaining cytoplasmic Vwa+ determinant remains a candidate for a regulatory system whose role in pathogenicity is expression of functions required for intracellular survival.